The Transition of Economy from Analogue to Digital in the XXI Century by the case of the Republic of Korea - Dok Hee OH; Aliaksei DANILCHANKA; Boris ZHALEZKA; Volha SINIAUSKAYA (Eastern European Journal of Regional Studies, 2021)
The article demonstrates the impact of digitalization on the political system and economy of the Republic of Korea based on the IT-revolution of the XXI century. Research methods used include comparative, system and logical data analysis, and the investigation of the digitalization trends. Data from Korean National Statistical Office and other official open sources are used for the determination of the main digitalization trends in the Korean economy. An analysis of specific phenomena arising in the economy and society as a whole is carried out under conditions of the digital economy. The evolution of the digitalization of hardware and software in the Republic of Korea is presented. The consequences of the transition of the economy from analogue to digital are revealed in such areas as the structure of the economy and business model, economic integration and liberalization, resource allocation and balanced development of regions, the role of government, and the intellectual property system.